ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.M UMUR 37 TAHUN DI PUSKESMAS KEJAJAR 1 WONOSOBO - Liyana, Liyana; Romdiyah, Romdiyah; Winarsih, Winarsih; Resmi, Dewi Candra (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
The worldwide maternal mortality rate (MMR) in 2020 was 223/100,000 KH and the IMR in 2020 was 27,975 per 1,000 live births (WHO, 2023). The government's efforts to reduce MMR and IMR with CoC are to provide continuous midwifery care with the SOAP method. The goal is to provide Comprehensive Midwifery Care that is carried out in Continuity of Care. The sample in the study is Mrs. M aged 37 years who will be studied from pregnancy, childbirth, LBW, postpartum and family planning. The implementation of case taking from March 14, 2024 to May 04, 2024. The results of research on pregnancy which was examined 3 times, found that Mrs. M had a high risk of pregnancy at the age of ≥35 years and hypertension in pregnancy. In Maternity Care Mrs. M experienced complications, namely precipitatus labor. There was no problem in the care of LBW. In Neonate Care, there was a problem, namely the baby had Neonatorum jaundice on day 10. In postpartum care and family planning there are no problems. The conclusion of this assessment is that midwifery care for pregnant women with high risk pregnancy ≥35 years and hypertension in pregnancy carried out on Mrs. M aged 37 years has received treatment and management according to midwifery care standards.